Production of Triacetin by Microwave Assisted Esterification of Glycerol Using Activated Natural Zeolite - Marwan Marwan; Eti Indarti; Darmadi Darmadi; Wahyu Rinaldi; Dzikri Hamzah; Taufik Rinaldi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Triacetin, an alternative biodiesel additive, was prepared by esterification of glycerol with acetic acid in the presence of chemically activated natural zeolite. The esterification was carried out in a small reaction flask under microwave irradiation. The catalyst was characterized for its morphology by SEM and its chemical composition by X-ray Diffraction (XRD). The Scanning Electron Microscopy (SEM) micrograph indicates improved surface area of the zeolite, while the XRD analysis shows an increase in Si/Al ratio from natural zeolite to 6.042 and its crystallinity value of 12.23%. The Fourier Transform Infra Red (FTIR) analysis obtained showed that microwave-heated samples have an esters group spectrum of triacetin at 1702 cm-1. The conversion value of glycerol was more than 95% at molar ratio of the reactants 1:9 and catalyst loading of 3%. The selectivities for monoacetin, diacetin and triacetin were 80.1%, 15.4%, and 4.5% at 60 minutes, and 43.0%, 48.6%, and 8.3% at 90 minutes. It shows that the conversion took place in consecutive steps and the use of microwave allows the reaction proceeding at milder condition.